2002
DOI: 10.1590/s0041-87812002000300008
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic/hyperoncotic solution in hypovolemic patients: experience in the emergency room

Abstract: Hypertonic solutions have been studied extensively in the treatment of hypovolemic shock, both in experimental and clinical models. Safety, efficacy, and long-term effects on animals and patients have been evaluated. The present article reviews indications, safety, mortality rates, and outcome in patients with hemorrhagic hypovolemic shock who were treated after admission with a hypertonic/hyperoncotic solution under strict observation in the emergency room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…Despite reports of initial hypotension with the rapid infusion of hypertonic saline solutions, the evidence shows that, overall, they may be of benefit in shock states [37]. Of the eleven trials focussing on trauma, single boluses of hypertonic saline were shown to increase blood pressure in six of these [38][39][40][41][42][43]. However, the methodological quality was considered poor in three of those studies [38,40,43].…”
Section: Blood Pressure Restoration In Shockmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite reports of initial hypotension with the rapid infusion of hypertonic saline solutions, the evidence shows that, overall, they may be of benefit in shock states [37]. Of the eleven trials focussing on trauma, single boluses of hypertonic saline were shown to increase blood pressure in six of these [38][39][40][41][42][43]. However, the methodological quality was considered poor in three of those studies [38,40,43].…”
Section: Blood Pressure Restoration In Shockmentioning
confidence: 99%
“…Of note, the patients were relatively healthy (for example, they were undergoing ASD or VSD repairs and did not have heart failure or dysrhythmias) and they did not have impaired right ventricular function. It remains to be shown if the volume-expanding effect of [39] RCT(1++) Trauma (pre-hospital) (166) 7.5% HSD vs RL Mortality, fluid balance, blood pressure** Younes [40] RCT (1)) Trauma (105) 7.5% HS vs HSD vs NS Mortality, fluid balance §, blood pressure** Vassar [41] RCT (1+) Trauma (258) 7.5% HS vs 7.5% HSD vs NS Mortality †, fluid balance, blood pressure Vassar [44] RCT (1+) Trauma (pre-hospital) (194) 7.5% HS vs 7.5% HSD vs 7.5% HSD (12%) vs RL Mortality †, blood pressure** Younes [42] RCT (1+) Trauma (212) 7.5% HSD vs NS Mortality †, fluid balance §, blood pressure** Alpar [43] RCT (1)) Trauma (180) 7.5% HSD vs RL Mortality, fluid balance §, blood pressure**-Bulger [65] RCT (1)) Trauma (209) 7.5% HSD vs RL Mortality, ARDS-free survival Wade [60] Meta-analysis Trauma (604) 7.5% HSD vs RL Mortality † Perel [62] Meta-analysis Trauma (1283) 7.5% HSD vs NS Mortality Wade [45] Meta-analysis Trauma (penetrating) (230) 7.5% HSD vs NS Mortality, blood pressure** Bunn [61] Meta-analysis Trauma, burns and general surgery (including head injury) (956)…”
Section: Cardiogenic Shock (Non-obstructive)mentioning
confidence: 99%
“…Although some studies have been performed using HS solution for treatment of hemorrhagic shock in a clinical set with stimulating results (38), its clinical application at the emergency room is not yet universally accepted. Nevertheless, its immune modulatory effects on I-R, described in experimental models, need more enlightenment.…”
Section: Figmentioning
confidence: 99%
“…The clinical use of HS solutions in fluid resuscitation has been investigated in many clinical settings, including trauma [16][17][18], shock [19][20][21], burn injury [22][23][24], raised intracranial pressure [25][26][27], and cardiac [28][29][30] and vascular [31,32] surgery. Although controversy persists regarding the beneficial effects of HS [33], a reduction in the mortality rate after its administration has been demonstrated in several studies [34][35][36].…”
mentioning
confidence: 99%
“…Although controversy persists regarding the beneficial effects of HS [33], a reduction in the mortality rate after its administration has been demonstrated in several studies [34][35][36]. Nevertheless, no clinical trials have been undertaken to investigate the effect of HS on patients undergoing major operations involving substantial blood loss, specifically orthopedic procedures.…”
mentioning
confidence: 99%